Evaluation of total phenolic content, antioxidant activities and sugarcontent of fresh mixed fruit and vegetables juices - Hasnah Haron,; Salsabila Hassan,; Chan, Boon Keng (Penerbit Universiti Kebangsaan Malaysia, 2017)
The notion of fruit and vegetables (FV) in preventing chronic diseases has long been discerned. To meet the recommended FV intake, FV juices have emerged as a convenient and healthy choice. Mixed fruit and vegetable juices (MFVJ) cater the blend of desirable flavor and taste of consumers. This study was carried out to determine the total phenolic content (TPC), antioxidant activities and sugar content of selected MFVJ. Folin-Ciocalteu assay was employed to quantify TPC, whereas DPPH and FRAP assays were used to evaluate the antioxidant activities of MFVJ. The sugar content was determined using phenol-sulfuric acid method. MFVJ extracted from bitter gourd, green apple and orange (BGO) had the highest TPC content (76.4 ± 4.2 mg GAE/100 ml). Celery and green apple (CG) juice showed the highest DPPH value (522.3 ± 7.6 mg TE/100 ml) whereas carrot and starfruit (AS) juice have the highest FRAP value (419.6 ± 21.6 mg TE/100 ml). The sugar content of MFVJ was within the range of 5.7-13.3 g/100 ml. MFVJ can be considered as healthy beverages with considerable amounts of phenolic compounds and low sugar content. This study provides some useful reference for consumers who consume juices with combinations of FV. Future studies need to discover more combinations of FV juices, providing more data pertaining to MFVJ. Identification of individual phenolic compounds should also be part of future research using various instrumental analyses.